A preliminary report on the prevalence and clinical features of allergic rhinitis in ankylosing spondylitis patients - Turgan, Arif; Ural, Ahmet; Ümit Işık, Abdülcemal; Arslan, Selçuk; Çapkın, Erhan; Ali Sarı, Refik (ENT Updates, 2015)
Objective: Our aim was to investigate the prevalence and clinical features of allergic rhinitis in patients with ankylosing spondylitis. Methods: This cross-sectional, clinical study was performed on 64 patients (24 females, 40 males) between October 2011 and November 2012. The Score for Allergic Rhinitis (SFAR) questionnaire was carried out to the patients with a recent diagnosis of ankylosing spondylitis. Skin prick test was performed to the cases who responded positively to SFAR. Descriptive parameters, clinical features and skin prick test results were documented. Results: The mean age of the study group was 41.7±11.2. Eight patients (12.5%) were presumably diagnosed for allergic rhinitis according to SFAR questionnaire. Skin prick test yielded positivity for Dermatophagoides farinae and Dermatophagoides pteronyssinus in one of the 8 cases who responded positively for SFAR. The most common symptoms were sneezing (n=15; 23.4%), nasal obstruction (n=12; 18.8%), and nasal itching (n=12; 18.8%). Conclusion: Our results demonstrate that prevalence of allergic rhinitis is lower in ankylosing spondylitis patients. However, clinical and pathophysiological features of allergic rhinitis accompanying autoimmune diseases must be investigated in further trials.